Knowledge and Attitudes Towards First Aid Measures Among Medical Students at Al-Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia - Alshuwayrikh, Abdulrahman (Sultan Qaboos Univ Med J, 2018)
OBJECTIVES: This study aimed to evaluate knowledge and attitudes towards first aid (FA) measures among medical students at the Al-Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia. METHODS: This cross-sectional study was conducted between September and December 2016 among 600 medical students in different academic years at Al-Imam Mohammad Ibn Saud Islamic University. Knowledge and attitudes towards FA measures were evaluated using a modified version of a previously validated questionnaire. Data were compared between students with previous FA training and those without previous FA training. RESULTS: A total of 259 medical students were included (response rate: 43%). Of these, 43% had previously received FA training and 63% had witnessed an emergency first-hand. Mean theoretical (5.93 ± 2.50 versus 4.49 ± 2.08; P <0.001) and practical (4.29 ± 2.62 versus 2.90 ± 2.17; P <0.001) knowledge scores were significantly higher among students with previous FA training compared to those without training; however, there was no significant difference in mean attitude score (5.60 ± 1.66 versus 5.39 ± 1.66; P = 0.329). CONCLUSION: The medical students, particularly those without previous FA training, demonstrated weak levels of FA knowledge. Such findings necessitate the inclusion of FA training in medical curricula in Saudi Arabia.